A quantum chemical study on the use of complexes between Hg(II) ions and fluorescent ligands for detection of cysteine - Nhan, Doan Thanh; Ai Nhung, Nguyen Thi; Hien, Nguyen Khoa; Quang, Duong Tuan (Vietnam Journal of Chemistry, 2017)
A benzothiazolium derivative as a fluorescent ligand was studied by the quantum chemical calculations, including research on the synthesis process, characteristics and applications. The calculated results showed that its complex with Hg(II) ions can be used as a fluorescent sensor for detection of cysteine. These findings have opened up opportunities for the use of previously reported complexes as well as new complexes between Hg(II) and fluorescent ligands for detection of cysteine. Keywords. Fluorescence, chemosensor, mercury, complexation, cysteine